Isolation, purification, and partial characterization of linamarase enzyme from the latex of java variety cassava (Manihot esculenta Crantz) - Medrocillo, Wilson F.
Linamarase enzyme was obtained by making an incision at the bark of the mature Java variety cassava. The enzyme obtained was extracted, isolated, purified, and partially characterized. It was isolated using the ammonium sulfate fractionation, and further purified using Sephadex G-50 in gel filtration chromatography. It was observed that the protein sample was purified by 2.52x higher purity than the pure cassava latex based on the purification fold and it was further purified by 270x for Fraction #3 and by 107x for Fraction #7. The results revealed that for every purification step, there was a loss of protein and yield using Bradford assay. The results showed that the yield of protein decreases as the purification proceeds, where the final yield was found to be 0.39% in Fraction #3 and 0.97% in Fraction #7 after the gel filtration chromatography. The linamarase enzyme from each purification step was partially characterized using Bradford Assay, SDS-PAGE, and its enzymatic activity.